Biochemical and histological evaluation of long-term consumption of buffalo and bovine colostrum in rats - El-Dieb, Samia (Indian Journal of Dairy Science, 2016)
This study was designed to evaluate the long-term consumption of Egyptian buffalo or Holstein cow colostrum on young Wistar rats. Buffalo and bovine colostrum were administered daily at 0.5 ml (low dose) or 1 ml (high dose)/100g body weight of rat for 90 days. The mean weight gain, muscle protein, blood chemistry parameters and histological examinations of the rats' liver and kidney were assessed at the end of the experimental period. Â The results showed that there was an increase in the mean weight gain in all treated groups relative to the control group. Total cholesterol of all treated groups at high dose was lower than the control group. An increase in HDL-cholesterol and IGF-1 was observed in all treated groups comparing with the control group. Kidney and liver functions did not affect by administration of both colostrums at two doses. Histologically, both colostrums at high dose caused some retrogressive changes in the rats' kidney; however, it has positive effect on the liver comparing with the control rats. It can be concluded that young growing rats has no observed toxicological and histological abnormalities caused by buffalo or cow colostrum administration particularly at low dose.